Delivering potable water: Beyond the policies. Issue 9 (1st September 2014) - Roberts, Megan G.; Long, Sharon C.
Abstract : Members of two AWWA committees team up to emphasize how water professionals provide the continuous attention needed to supply safe drinking water to the public.